Sleep and Movement Differentiates Actions of Two Types of Somatostatin-Expressing GABAergic Interneuron in Rat Hippocampus - Katona, Linda (Cell Press, 2014)
Neuropeptides acting on pre- and postsynaptic receptors are coreleased with GABA by interneurons including bistratified and O-LM cells, both expressing somatostatin but innervating segregated dendritic domains of pyramidal cells. Neuropeptide release requires high-frequency action potentials, but the firing patterns of most peptide/GABA-releasing interneurons during behavior are unknown. We show that behavioral and network states differentiate the activities of bistratified and O-LM cells in freely moving rats. Bistratified cells fire at higher rates during sleep than O-LM cells and, unlike O-LM cells, strongly increase spiking during sharp wave-associated ripples (SWRs). In contrast, O-LM interneurons decrease firing during sleep relative to awake states and are mostly inhibited during SWRs. During movement, both cell types fire cooperatively at the troughs of theta oscillations but with different frequencies. Somatostatin and GABA are differentially released to distinct dendritic zones of CA1 pyramidal cells during sleep and wakefulness to coordinate segregated glutamatergic inputs from entorhinal cortex and CA3.